A mensuração da precariedade habitacional em pequenos municípios brasileiros: um estudo sobre os assentamentos dos mais pobres em Marechal Deodoro, Alagoas - Machado, Bruna Maria Ferrari (2012)
The present work has as an overall matter of the poorest precarious housing in small municipalities. It focuses the phenomenon of precarious settlements in Brazil and the different methodologies used for measuring this precariousness. The research has as an empirical purpose the housing situation of the poorest, in Marechal Deodoro, Alagoas, in the northeast region of Brazil. On this point, we see that it is necessary to deepen the knowledge on housing instability in this country, especially in small municipalities, since the measuring methodologies of research national institutions have not been able to translate the Brazilian reality in their distinct specifications. At first, we discuss the configuration of the poorest housing spaces in Brazil. Then, we discuss the new National Housing Policy (NHP) and the Local Plan for Social Housing (LPSH) as important tools to increase knowledge about instability in poor housing. Afterward, we discuss about the precarious settlements and the challenges and advances in measuring the housing in Marechal Deodoro, Alagoas, pointing to data from national measuring methodologies (IBGE, CEM/CEBRAP e FJP) and those found in the empiric research. It is argued in this work that the identity of the poorest precarious housing in Brazil faces problems, particularly in small Brazilian municipalities. The methodologies of national survey institutions on precarious housing, and housing needs (IBGE, CEM/CEBRAP e FJP) present results that underestimate the actual conditions of precarious housing. In this point, we emphasize the importance of the role of LPSH in knowledge and characterization of the poorest precarious housing, and surveys conducted by the municipalities themselves, in elaborating public policies that communicate with local specifications in several Brazilian cities.